Securing Access to Academic Information Systems with WhatsApp-Based OTP: Implementation at Senior High School - Nelsen Septa Henidar; Achmad Fauzan; Ridho Muktiadi; Lahan Adi Purwanto Wijaya; Tresna Yudha Prawira (Journal of ICT, Design, Engineering and Technological Science, 2024)
Development transformation in the digital age provides some changes, one of which is in security aspects. One of the methods that can enhance security is applying the two-factor authentication (2FA) method through a one-time password (OTP) code as an extra level of credibility. The use of WhatsApp API through a third-party API provider named Fonnte was applied to the college information system of Purwokerto Senior High School. With its integration of Fonnte API, it can deliver OTP codes in real-time within an average time delay of 1.2 seconds, which is sent through WhatsApp, a favorite instant app that is easily accessed through social groups. The implementation in question is made in order to enhance user data security and avoid unauthorized access. The result of the experiment reveals that two-factor authentication use through OTP is successful in sending OTP within a short response time and achieving results through administering a questionnaire for 10 respondents, which acquired 82.6 results in the category of Strongly Agree.